Effectiveness of Atraumatic Care Approach: Swaddle and Sponge Bath on Vital Signs and Pain Scale in Neonates - Dior Manta Tambunan; Lenny Lusia Simatupang (Jurnal Keperawatan, 2024)
The newborn's transition from an intrauterine to an extrauterine environment can increase stress. One of the treatments for newborns that is often neglected and causes trauma to infants is bathing. The purpose of the study is to determine the difference in effectiveness between swaddle and sponge bath on newborns' vital signs and pain thresholds. The study used a Quasi-Experimental Design with 2 groups Pre and Post-Test at Private Primary Clinic. The total sample of 32 neonates was divided equally into the swaddle and sponge bath groups. Data was analyzed by Paired T-Test, Independent T-Test, Wilcoxon Test, and Mann-Whitney Test based on data normality. The study defined that there was a significant difference in respiration rate, heart rate, oxygen saturation, body temperature, and pain scale at 5 minutes postbath with a p-value was <0.05 in both groups. The study concluded that a swaddle bath was considerably helpful, safe, protected, and stress-free in stabilizing vital signs and pain scales in neonates. Swaddle bath as part of developmental care to improve approach of the atraumatic care as a standard bathing technique. It is recommended that further research be done to add crying times and stress levels to the swaddle and sponge bath method.